Evaluation of furniture used by old people in sitting - Maria Luísa Guillaumon Emmel; Luciana Bolzan Agnelli Martinez; Luiza Oliva Paganelli (O Mundo da Saúde)
Aging is a dynamic and progressive process, in which there are morphological, functional, biochemical and psychological changes that lead to greater vulnerability and higher incidence of pathological processes. Considering this, one sees the need to provide some care for promoting a healthy aging. A portion of the elderly population remains much of their day in a sitting position and this can harm their health, since their routine must be balanced with physical activity and a variety of approaches. Even with the reduction in the time they remain seated, if they do not adopt a correct position and/or use suitable furniture, the consequences may be even more harmful for the elderly. This work aimed to evaluate furniture present in houses for the elderly, in order to verify their main dimensions and characteristics, as well as to identify the main inadequacies and see whether there were and what were the adjustments made by the elderly themselves. Following a preventive approach, we selected 25 active seniors, aged 60 to 83 years. For data collection, two scripts to be applied were built. A plurality of furniture was found and organized into five different categories. All categories presented inadequacies: 100% of furniture was appropriate concerning seat width, but only 24% were in compliance with their height and 80% in inadequate seat depth measurement. 52% of the evaluated furniture presented some type of adjustment made by the elderly to improve their posture and / or feel more comfortable when sitting. These results point to the need to adapt these to prevent discomfort and some diseases, especially musculoskeletal and circulatory system ones.